Rooms of Their Own : Eddy Sackville-West / Virginia Woolf/ Vita Sackville-West. - Strachey, Nino (Londen : Pitkin Publishing, 2018)
Woolf, Virginia ; Sackville-West, Eddy ; Sackville-West, Vita ; Bell, Vanessa ; Grant, Duncan
Bloomsburry, shifting social and morals attitudes towards gender and sexuality in 1920s and 1930s UK. Monk's House.
boek